Omega polynomial revisited - Diudea, Mircea V. (Acta chimica slovenica, 2010)
Omega polynomial was proposed by Diudea (Omega Polynomial, Carpath. J. Math., 2006, 22, 43-47) to count the opposite topologically parallel edges in graphs, particularly to describe the polyhedral nanostructures. In this paper, the main definitions are re-analyzed and clear relations with other three related polynomials are established. These relations are supported by close formulas and appropriate examples.
Keywords: chemical graph theory; CI indeks; CI index; Cluj-Ilmenau indeks; Cluj-Ilmenau index; counting polynomials; kemijska teorija grafov; matematika; mathematics; Omega polinom; Ommega polynomial; PI indeks; PI index; Pi polinom; Pi polynomial; Sadhana polinom; Sadhana polynomial; Theta polinom; Theta polynomial